Soil amplification factors at the seismographic network stations sites in morocco from seismic ambient noise - Ouchen, Ibrahim; El. Fellah, Younes; Khairy Abd El- Aal, Abd El-Aziz; Harnafi, Mimoun (International Journal of Engineering and Technology, 2018)
Knowledge of the soil response to seismic activity allows to better incorporate the constraints of seismic risk reduction. The experimental methods employed to determine site effects seek to obtain seismic amplification parameters by means of measuring earthquakes or seismic background noise. In this work, we present the main set of results of the microtremor data analysis based on the horizontal-to-vertical (H/V) spectral ratio technique at broadband seismic stations in order to get the fundamental site frequency (f0) and its associated amplitude of ground motion (A0). These stations were deployed in different structural domains: Rif, Middle, High and Anti Atlas Mountains. This study was carried out using the Nakamura technique, based on the measurements of background noise at each measurement site. Nakamura's method makes it possible to evaluate the effect of the superficial layers on the seismic signal. The f0 (H\V) values were used in the calculation of bedrock depth at measured sites. The thickness of unconsolidated sediments at the investigated sites was determined. The parameters obtained in this work allowed us to highlight a set of distribution figures of fundamental frequency (f0), amplification (A0) (H/V) and soft sedimentsÂ thickness throughout the location of study and to show the agreement with geological setting.Â Keywords: H\V spectral ratio, amplification factor, frequency wavenumber, Thickness of sediments